PLIKASI ONLINE SISTEM MANAJEMEN BERKAS PELAYANAN BERBASIS WEB PADA KANTOR PELAYANAN PAJAK BUMI DAN BANGUNAN KOTA SEMARANG (Information Technology and Telematics, 2016)
ABSTRAKKantor  Pelayanan  Pajak  Bumi  dan  Bangunan  Kota  Semarang mempunyai  tugasmelaksanakan urusan  rumah  tangga  Pemerintahan  Daerah  dan  tugas  pembantuan  di  bidangpendapatan,  pengelolaan  keuangan  dan  aset  daerah  diantaranya  pembayaran  pajak  bumi  danbangunan.  Pajak  bumi  bangunan  merupakan  pajak  yang  dipungut  oleh  pemerintah  kepadasemua  kalangan masyarakat,  dimana  hasil  dari  penerimaan  pajak  bumi  dan  bangunandigunakan untuk pembangunan fasilitas umum yang bermanfaat bagi masyarakat umum.Metode  pengembangan  sistem  dalam  penelitian  ini  adalah  Waterfall  dengan  tahapanpermulaan  sistem,  analisis sistem,  perancangan  sistem  dengan  menggunakan  UMLdan implementasi sistem dengan menggunakan PHP dan MySQL .Hasil dalam penelitian ini adalah terbentuknya sistem manajemen berkas secara onlineuntuk  pengelolaan dan  verifikasi berkas  pelayanan  pajak  bumi  dan  bangunan  pada  KantorPelayanan Pajak Bumi dan Bangunan Kota Semarang yang dapat memberikan data rekapitulasitentang berkas masuk dan berkas keluar dari berkas pelayanan PBB dalam bentuk grafik dantabel dan dapat menampilkan informasi pelayanan PBB dalam bentuk tabel secara realtime.Kata Kunci : Pelayanan Pajak, Pajak Bumi dan Bangunan, Manajemen Berkas, ABSTRACTSemarang  as the  capital  city  of  Middle Java  Province  have several  working  units  toensure that daily activity are run smoothly. One of the working unit is called as Finance andAssets  Management  Authority.  The  scope  of  the  area  are  city  incomes,  finance  managementand also asset management. Aligned with the scope of the city income management, Semaranglocal  government  impose  a  tax  interest  in  real  property  (land,  buildings,  and permanentimprovements). This kind of tax are considered under state law to be ownership interests.Themain purpose of this land and buildings tax is to be the backbone income of the city. with agood management, it will be very important to run the city in order to reach city welfareness.With  good  income,  social  facility  and  other  society  support  could  be  well  established  inSemarang.In  order  to  support  the land  and  building tax  program  in  Semarang,  the  journalpropose  to  develop  improvement  program.  This  study  using  Waterfall Method withimplementation step using PHP and MySQL. Those PHP and MySQL will be the key systems toensure that the programs are well implemented.The  objectives  of  this  study  is  to  develop  online  document  management  system  tomanaging and verify the land and buildingstax documents. The program will provide real-timedata  for  any  process  which  starting  from  receiving  documents,  verification until  it  doneprocessed.  The  data  will  be  much  more  easy  to  analyze  since  the  graph  and  table will  bedisplayed under real-time data.Key Words : Tax Services, Land and Buildings Tax, Files Management